2017
DOI: 10.1111/aji.12621
|View full text |Cite
|
Sign up to set email alerts
|

The lack of natural processes of delivery and neonatal intensive care treatment lead to impaired cytokine responses later in life

Abstract: The lack of natural processes of delivery and neonatal intensive care treatment might lead to long-lasting impairment of immune responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…A few studies regarding CRP have been described, that found similar differences in new-born levels depending on birth form as we describe (33,34). In a study among teenagers, whose mothers had entered the active phase of labour before CS, spontaneous and toll-like receptor-stimulated cytokine release was increased, compared to controls born by pre-labour CS (35). This concurs with another study showing that the risk for early childhood infections are higher in children born by pre-labour CS compared to children born by in-labour CS or VD (1,36).…”
Section: Discussionsupporting
confidence: 62%
“…A few studies regarding CRP have been described, that found similar differences in new-born levels depending on birth form as we describe (33,34). In a study among teenagers, whose mothers had entered the active phase of labour before CS, spontaneous and toll-like receptor-stimulated cytokine release was increased, compared to controls born by pre-labour CS (35). This concurs with another study showing that the risk for early childhood infections are higher in children born by pre-labour CS compared to children born by in-labour CS or VD (1,36).…”
Section: Discussionsupporting
confidence: 62%
“…Similar evidence has been brought regarding the mode of delivery on the composition of neonatal gut microbiota, and the maturation of the intestinal epithelium capable to control the immune system during early life (23). Newborns delivered by cesarean may have an early microbiota alteration and consequently different patterns of the immune response (24) even a long-lasting impairment of immune status (25). Our study provides evidence that birthweight may have a limited role in the risk to JIAPs knowing that fetal growth and timing of birth may be factors of the susceptibility to JIA (26).…”
Section: Discussionmentioning
confidence: 89%
“…A few studies regarding CRP have been described, which found similar differences in newborn levels depending on birth form as observed in the current study ( 30 ). In a study among teenagers, whose mothers had entered the active phase of labor before CS, spontaneous and toll-like receptor-stimulated cytokine release was increased, compared to controls born by pre-labor CS ( 31 ). This concurs with another study showing that the risk for early childhood infections is higher in children born by pre-labor CS compared to children born by in-labor CS or VD ( 32 ).…”
Section: Discussionmentioning
confidence: 98%